La mujer en el Conventus Asturum. Su reflejo epigráfico (Estudios humanísticos. Geografía, historia y arte, 1994)
During the Roman period women were a very important element for the process of romanization.In this article I would like to offer a global vision of women, both, the roman and the indigenous ones, in the Conventus Asturum, and therefore it has been revised the epigraphy where appears women's names such as funerary, votiv, honorific and monumental inscriptions, from this part of Roman Empire.